The European peripherality index - Carsten Schürmann; Ahmed Talaat (European Regional Science Association (ERSA), 2002)
Article 2 of the Maastricht Treaty states as the goals of the European Union the promotion of harmonious and balanced economic development, convergence of economic performance, improvement of the quality of life and economic and social coherence between the member states. A prominent role for the achievement of these goals play the envisaged Trans-European Transport Networks (TETN). They are to link landlocked and peripheral areas with the central areas of the Community. The identification of those peripheral regions, whose accessibility and transport infrastructure systems are to be improved, is becoming of great political importance. This is underlined by the European Commission's first Cohesion Report (1997) which emphasises that "regions should ensure that policy success is measurable, that results are regularly monitored, and that the public and political authorities are regularly informed of progress." This paper presents the results of a study on peripherality undertaken for the European Commission. The purpose was to undertake, for the fifteen EU states and twelve candidate countries, the calculation of an index of peripherality of the 'potential' type. The economic potential of a region is the total of destinations in all regions weighted by a function of distance from the origin region. It is assumed that the potential for economic activity at any location is a function both of its proximity or 'travel tim' to other economic centres and of its economic size or 'mass'. The influence of each economic centre on any other centre is assumed to be proportional to its volume of economic activity and inversely proportional to a function of the distance between them. The economic potential of a given location is found by summing the influence on it of all other centres. Based on theoretical considerations, an integrated European Peripherality Index software system was developed to facilitate peripherality indices calculatio scenarios comparison, data updating and results demonstration. It is designed in a way to evaluate the impacts of transport infrastructure projects as well as impacts of general transport policies with respect to peripherality and could be seen as a first attempt for a wider regional monitoring system. In this, it should contribute to answer the debated question whether infrastructure improvements rather lead to cohesion effects or whether they increase disparities between the regions. The paper starts with theoretical considerations on cohesion effects of transport infrastructure improvements and concepts of accessibility and peripherality. Then the methodology used and the software system developed will be addressed briefly. Eventually the results of the indicator calculations will be presented, before the paper concludes with political implications and findings.
Keywords: 330